An experimental and density functional theory studies of Nb-doped BiVO4 photoanodes for enhanced solar water splitting - Kalanur, Shankara S.; Seo, Hyungtak (Journal of Catalysis, 2022)
In this work, the influence of Nb doping on the photoelectrochemical (PEC) water splitting activity of monoclinic BiVO4 photoanode is explored using experimental and theoretical studies. A facile hydrothermal method is proposed for the synthesis of Nb-doped BiVO4 nanostructured thin films and detailed characterization was carried out to understand the morphology, crystal structure, optical, band edge, and electrochemical properties. The PEC studies revealed that the doping of Nb brings about a fourfold enhancement in BiVO4 photocurrent reaching ∼ 2.01 mA cm−2 at 1.23 V vs reference hydrogen electrode (RHE). The doping of Nb was found to increase the carrier density in the bulk of BiVO4 and improve the charge separation, charge transfer, diffusion, and decrease the charge transfer resistance at the BiVO4/electrolyte interface. Importantly, a charge separation efficiency of ∼ 98% was achieved (at 1.23 V vs RHE) with a photocurrent density of ∼ 4.5 mA cm−2 (with hole scavenger) and stoichiometric H2/O2 evolution (2:1) upon Nb doping. Furthermore, the density functional theory (DFT) calculations indicated changes in bandgap and density of states which agree with the experimental results indicating favorable transformation in the bulk and surface properties of BiVO4 after the Nb substitution.
Keywords: Charge-separation; Density functional theory studies; Hydrogen electrodes; Monoclinics; Nb doped; Nb doping; Photo-anodes; Photoelectrochemical water splitting; Solar water splitting; Water splitting; Band structure; BiVO4; DFT studies; Niobium; Water splitting